Analisis Faktor Penyebab Kecacatan Proses Pengeringan Teh Hijau Menggunakan Metode Six Sigma dan FMEA di PT. Candi Loka - Tutut Vita Nuraini; Didiek Hermanuadi (Jurnal Teknik Pertanian Terapan, 2023)
The drying process is a process carried out to reduce the moisture content of green tea leaves, and to reduce the presence of microbial growth and enzyme activity. Final drying uses a Ball Tea machine at PT. Candi Loka. The purpose of this research is determine the value of the sigma level in the green tea drying process, determine the factors can affect defects, and identify ways to reduce or minimize the occurrence of defects in the green tea drying process at PT Candi Loka. This research uses Six Sigma and FMEA methods with DMAIC (Define, Measure, Analyze, Improve, Control) stages used to improve the quality of the green tea drying process at PT Candi Loka to minimize defects that occur. The results of the calculation of DPMO and the sigma value obtained are the overall process DPMO value of 3.1 sigma value. Based on the fishbone diagram, the factors that affect defects are human factors, machine factors, and material factors. Based on the analysis using the FMEA method, it is known that the highest RPN value in the failure mode is 48, and the failure mode of performance decreases by 36.